2019
DOI: 10.1371/journal.pone.0208154
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices of hepatitis B prevention and immunization of pregnant women and mothers in northern Vietnam

Abstract: Background and aim Infection at birth due to mother-to-child (MTC) transmission is the most common cause of chronic hepatitis B virus (HBV) infection in Vietnam. This study was undertaken to examine the knowledge, attitudes, and practices of pregnant women and mothers in Vietnam concerning HBV prevention and immunization. Methods A cross-sectional survey was conducted in Quang Ninh and Hoa Binh provinces in 2017. A standardized questionnaire was administered to women wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 19 publications
3
19
1
Order By: Relevance
“…That is to say, 80.1% of the participants were likely to allow their children's vaccination. This attitude is similar to that of Vietnam and China, 86% and 89%, respectively [19,28]. This finding could be explained by HBV vaccines being included in the vaccination schedule of children by the ministry of health.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…That is to say, 80.1% of the participants were likely to allow their children's vaccination. This attitude is similar to that of Vietnam and China, 86% and 89%, respectively [19,28]. This finding could be explained by HBV vaccines being included in the vaccination schedule of children by the ministry of health.…”
Section: Discussionsupporting
confidence: 73%
“…For instance, only 47% of participants recognized that HBV is transmitted by blood compared to 85.8% in Vietnam [19], 46% to 75% in China [14,20], and 10% in Nigeria [21]. Only about 28% of the participants were aware of sexual transmission compared to 75% in Vietnam, 46% to 52% in China, and 41% in Nigeria [14,[19][20][21]. Although it is considered routine to test for HBV during the antenatal visits [22], it is necessary to educate pregnant women on the risks of infection and the means of transmission, in addition to emphasizing the benefits of vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…The rates of using preventive measures such as BDV, HBIG immunization, and HBV vaccination observed in Haiphong are higher than those observed in neighboring countries [ 28 , 30 , 38 , 39 ] and around the world [ 8 , 40 , 41 ]. They are also higher compared to recent rates reported from other provinces in Vietnam [ 18 20 ] or from national estimates [ 40 , 42 , 43 ]. Different studies found that despite implementation of appropriate immunization programs, about 8–30% vertical transmission still occurs in infants born to HBeAg-positive women [ 27 , 44 , 45 ].…”
Section: Discussioncontrasting
confidence: 63%
“…For instance, pregnant women in the sample tend to come from the city of Haiphong, one of the largest urban agglomerations of Vietnam. Women had a higher monthly income compared to the national level of <2800 USD/capita/year in 2019 and had a higher education level compared to those observed in other population studies [ 18 20 ]. Several studies have shown that a low socioeconomic status was a risk factor for HBV infection [ 21 ].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation